Pengaruh Problem-Based Flipped Learning Terhadap Berpikir Kritis dan Kreatif Siswa Dalam Pembelajaran PAI - Mohamad Irsan Hadi; I Komang Sudarma; I Kadek Suartama; Ni Nyoman Parwati; I Made Tegeh (Cetta: Jurnal Ilmu Pendidikan, 2026)
The 21st century demands students to develop critical and creative thinking skills, yet Islamic Religious Education (PAI) learning in schools still tends to be teacher-centered. This quasi-experimental research with a pretest-posttest non-equivalent control group design aimed to examine the simultaneous and partial effects of the Problem-Based Flipped Learning(PBFL) model on students' critical and creative thinking skills compared to the Direct Instruction model. The study involved 64 eighth-grade students at SMP IT Al Hasaniyah NW Jenggik, selected through group random sampling. Data were collected using valid essay tests and analyzed using Multivariate Analysis of Covariance (MANCOVA) by controlling for students' initial abilities (pretest). The multivariate results indicated that the PBFL model had a significant simultaneous effect on students' critical and creative thinking skills (p < 0.001). The partial eta squared effect size fell into the very large category, proving the model's dominant practical effectiveness. Partially, the PBFL model also exerted a significant and strong effect on both critical thinking (p < 0.001) and creative thinking skills (p < 0.001). This superiority was evident in students' sharp analysis from elementary clarification to strategic levels, alongside fluency in designing original theological solutions. In conclusion, integrating technology-assisted pre-class self-directed learning and authentic problem-solving within the PBFL model successfully accelerates students' higher-order thinking skills (HOTS) in PAI subjects.